Elaboração e caracterização de pão sem glúten - Lara, Cristiane Ferreira de (2018)
The development of a gluten-free bread proves to be too complex to obtain pleasant sensory characteristics. Gluten is an important protein in breads, because it provides softness, elasticity and helps fermentation, but when it comes to celiac, gluten is toxic. There for the accomplishment of a work that seeks to help and present new options of gluten-free bread, is of extreme importance. This work has as main objective, to elaborate a gluten-free bread, which proposes new ingredients and the search for a technique to arrive at a near recipe and similar to the normal loaves that contain gluten. Two formulations were made, one developed using the scald technique and another using ingredient accessible to celiacs. Aw, color, texture and volume analyzes were done only in formulation 2, which presented better sensorial characteristics. The results obtained were on average 0.9319 for Aw, for shell color the mean values were 46.76 for the parameter L *, 10.95 for the parameter a * and 13.51 for the parameter b *, already the core had mean values of 60.63 for the parameter L *, 3.29 for the parameter a * and 17.07 for the parameter b *. The texture obtained an average value of 4695g and the volume had a difference of 240cm³. The first formulation that was obtained by the scald technique was not adequate, since its consistency was rigid and compact.